Comparison of physiological responses to an incremental running test on treadmill, natural grass, and synthetic turf in young soccer players - Di Michele, R.; Di Renzo, A.; Ammazzalorso, S.; Merni, F. (The Journal of Strength and Conditioning Research, 2009)
This study aimed to compare the physiological responses to a running test often used to assess lactate thresholds in soccer players when performed with an identical protocol on treadmill (Tr), natural grass (Nat), and synthetic turf (Synt). Eighteen young soccer players (mean ± SD: age, 17.4 ± 0.8 years; body mass, 66.2 ± 6.7 kg; height, 175.8 ± 5.7 cm) performed on each surface a multistage running test, including 4-minutes stages separated by a 1-minute rest, with initial speed set at 8 km/h and increased of 2 km/h after each stage. Blood lactate concentration (La) and heart rate (HR) were assessed. The test ended when La exceeded 4 mmol/L. At each of the stages completed in the three conditions by all the subjects (8, 10, 12, and 14 km/h), La was higher in Synt vs. both Nat and Tr with differences of at least 0.6 mmol/L (p < 0.05), whereas HR was higher (p < 0.05) in Synt vs. Nat with differences from 4.3 b/min (at 10 km/h) to 6.4 b/min (at 8 km/h). Running speed at the 4 mmol/L La threshold was lower (p < 0.05) in Synt (13.1 ± 1.1 km/h) than in Nat (13.9 ± 1.2 km/h) and Tr (14.4 ± 1.3 km/h). The La/HR curve obtained in Synt was shifted upward compared with the Nat and Tr curves, indicating higher La values at given HRs. These results could be mostly explained by adaptations of running mechanical patterns to surface properties that affect the energy requirements of running. This study emphasized the importance of testing soccer players on the specific surface used for training activities when assessing lactate threshold indices to prescribe and monitor field training.